Pengaruh Variasi Menu Terhadap Keputusan Mahasiswa Dalam Pembelian Makanan Dan Minuman Online Di Aplikasi Grabfood - Wahyu Ratnasari; Dinar Rosiana Febrianti (Departement of Mathematics Education, 2024)
This study aims to explore the influence of food and beverage menu variety on students' purchasing decisions when using the GrabFood application. Menu variety is considered a crucial factor that may affect consumers' preferences and purchasing decisions in the context of online food and beverage purchases. The research method employs simple linear regression to analyze data collected from 69 student samples who are GrabFood application users, selected from the population of students using the application at a university campus. The results of data analysis indicate a positive and significant influence of food and beverage menu variety on students' purchasing decisions in the GrabFood application, highlighting the importance for service providers like GrabFood to expand menu variety to enhance consumer satisfaction and loyalty, as well as to strengthen the company's position in the online food delivery industry. Therefore, recommendations are provided to continuously improve menu variety in the application, and to further understand consumer preferences and needs to enhance purchasing decisions and strengthen the company's market position.